Controlling Model For Risk Factors Of Stunting Incident - Eva, Lisma Evareny; Abbas, Hasriwiani Habo; Bachtar, Fitrina (Window of Health : Jurnal Kesehatan, 2024)
Stunting is the condition where the children have stunted growth and development refers to weight/age (TB/U). In 2015-2017, there were 19,4%, 18,9% and 21,3% cases in West Sumatra. Pasaman district had the highest percentage of stunting from 19 Cities in West Sumatera, which is 21,1%, 25,7%, and 25% cases. The purpose of this study was to analyze the risk factor control model for stunting in toddlers in the Pasaman district. This study was an observational analytic study with an unmatched case-control design. The subject of this study was the 35 families who had children 12-59 months with stunting cases and another 35 group control in Pasaman district. Data were collected by using a questionnaire to measure stunting risk factors. Data was analyzed by using univariate, bivariate, and multivariate analysis with regression and backward methods. The result of the study showed that “father education level” as a stunting risk factor had a P value=0,048 and “family income” with P value = 0,015, while history of birth weight had a P value of 0,08. The final result (sixth step) showed that the baby's birth weight variable had the odds ratio eβ=31,578 when analyzed simultaneously with another variable (parenting and father’s education level). Conclusion: baby birth weight variable simultaneously with parenting and the father’s educational level affected the incident of stunting in toddlers (eβ=31,578). It is necessary to increase family empowerment to control the cases of stunting related to the nutrition of pregnant mothers by improved child care, parenting in feeding, and increased family income.